The Influence of Principal Leadership on the Satisfaction with Early Childhood Education Services Quality - Citra Aulia Uzliva; Hilmi Qosim Mubah; Ach. Baidowi; Retno Wuri Sulistyowati; Diah Harmawati (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The interactions among teachers, facilities, leadership, and administrative systems influence the quality of educational services. A holistic approach is necessary to understand how morale, cooperation, professional practices, and facility management improve the effectiveness of early childhood education services. This study aims to analyze the effect of school principal leadership on the quality of Early Childhood Education services. The research used a quantitative correlational method with questionnaires administered to 35 respondents. Data were analyzed using SmartPLS through validity, reliability, and t-statistics tests to ensure the instruments' accuracy and the significance of variable relationships. The research findings revealed that school principal leadership (SPL) had a positive and significant impact on service quality (SQ), with an Original Sample of 0.791, a T-statistic of 17.960, and a P-value of 0.000. This indicates that morale, cooperation, active and professional learning, as well as the utilization and maintenance of equipment, play a significant role in creating quality administrative services and optimizing the use of school facilities. In conclusion, SPL significantly influences SQ, suggesting that morale, cooperation, professional learning, leadership, and the use of facilities are crucial in improving administrative service quality and overall school effectiveness.